Use of noninvasive ventilation for acute respiratory failure in intensive care unit. - Melo, Flávio Emanoel Souza de; Nogueira, Ivan Daniel Bezerra; Felismino, Amanda Soares; Vicente, Ridyuane Narah Imperiano dos Santos; Silva, Ivanízia Soares da; Nogueira, Patrícia Angélica de Miranda Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: The noinvasive ventilation (NIV) has been an important resource for the management of acute respiratory failure (ARF) in intensive care unit (ICU). Several factors related to the patient, the healthcare team and the equipment used can influence in the success or failure of this therapy. Therefore, it is beneficial to analyze the use and effectiveness of NIV in everyday practice, which may lead to shorter hospital staying, reduce costs, and decrease mortality rate. Objective: To observe the use of NIV in patients with ARF in ICU. Methods: Prospective and observational study, assessing 37 patients aged over 18 years, who undergone NIV in ICU for ARF. The volunteers were assessed for clinical characteristics, physiological parameters, and outcome. The sample was divided into success group - SG (nonintubated patients after NIV use) and failure group - FG (intubated patients after NIV use). Results: The NIV was successful in 18 (48.6%) subjects and failed in 19 (51.4%) of them. Acute pulmonary edema was the main reason (62.4%) of ARF found. The FG compared to SG showed longer duration of NIV use (p = 0.05), lower arterial pH (p = 0.00), higher PaCO 2 (p = 0.02) greater accumulated water balance within 24 hours (p = 0.03) and 72 hours (p = 0.05) prior to the last use of NIV. It was also observed that the FG patients had higher hospital mortality rate, as follows: 73.8% versus 16.7% of FG SG (p = 0.00). Conclusion: The FG had a longer ICU staying and higher mortality rate. Moreover, the consciousness levels, the pH level, PaCO 2 and cumulative fluid balance appear to contribute to the success or the failure of NIV.